Automated system for detecting jute plant disease using image processing and machine learning integrated with mobile application - Joyee, Faiza Nuzhat; Mahsa, Nuzhat Ashraf; Reza, Zarreen Naowal (BRAC University, 2016)
Cataloged from PDF version of thesis report.